2022
DOI: 10.26434/chemrxiv-2022-m32fb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing the Performance of Layered Metal-Organic Framework Supercapacitors by Coordination Modulation

Abstract: Metal-organic frameworks (MOFs) are among the most promising materials for next-generation energy storage systems, including supercapacitors. Few studies, however, have examined the impact of particle morphology and degree of agglomeration on the energy storage performances of these materials. To address this, here we use coordination modulation to synthesise three samples of the conductive MOF Cu3(HHTP)2 (HHTP = 2,3,6,7,10,11-hexahydroxytriphenylene) with distinct microstructures. Evaluation of the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This finding supports the cation-dominated charging mechanism proposed from theoretical and experimental work for the related MOF Cu3(HHTP)2. 12,13 Therefore, whilst in-pore anion concentration was earlier shown to serve as a useful indicator of electrolyte-accessible pore volume and hence electrochemical performance (Figure 4e), the anions themselves are not primarily responsible for the charge storage in these systems.…”
Section: Ex-situ Nmr Charging Experimentsmentioning
confidence: 97%
See 2 more Smart Citations
“…This finding supports the cation-dominated charging mechanism proposed from theoretical and experimental work for the related MOF Cu3(HHTP)2. 12,13 Therefore, whilst in-pore anion concentration was earlier shown to serve as a useful indicator of electrolyte-accessible pore volume and hence electrochemical performance (Figure 4e), the anions themselves are not primarily responsible for the charge storage in these systems.…”
Section: Ex-situ Nmr Charging Experimentsmentioning
confidence: 97%
“…Interestingly, the cation dominated nature of this charging mechanism is consistent with EQCM studies on the related MOF Cu3(HHTP)2 with 1 M NEt4BF4/ACN electrolyte. 13 The greater contribution of the cations compared to anions in charge storage of these systems suggests that the cation identity may be most closely linked to the overall electrochemical performance. Gittins et al previously demonstrated the impact of increasing the alkyl chain length in this family of cations, but further exploration of electrolytes is needed to improve electrochemical performance beyond that for 1 M NEt4BF4/ACN electrolyte.…”
Section: Operando Eqcm Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the cation-dominated charging mechanism proposed from theoretical and experimental work for the related MOF Cu3(HHTP)2. 12,13 Therefore, whilst in-pore anion concentration was earlier shown to serve as a useful indicator of electrolyte-accessible pore volume and hence electrochemical performance (Figure 4e), the anions themselves are not primarily responsible for the charge storage in these systems.…”
Section: Ex-situ Nmr Charging Experimentsmentioning
confidence: 97%
“…Electrochemical quartz crystal microbalance (EQCM) experiments were used to experimentally study the same MOF-electrolyte system employed in the QM/MM study above, Cu3(HHTP)2 with 1 M NEt4BF4/ACN, and supported the cation dominated nature of the charging mechanism. 13 More widely, He et al performed in-situ small-angle neutron scattering (SANS) experiments, on Ni3(HITP)2 cells with an organic electrolyte of sodium triflate in dimethylformamide (DMF). 14 The charging mechanism was found to be dependent on the electrode polarisation and the MOF was proposed to be ionophobic with respect to this electrolyte, with the pores devoid of electrolyte ions in the absence of an applied potential, a scenario which has been predicted to lead to improved performance in nanoporous carbon supercapacitors.…”
Section: Introductionmentioning
confidence: 99%